Comparison of physical demands between positional games and matches in elite soccer players - Vilamitjana, Javier; Heinze, Gabriel; Verde, Pablo; Calleja-Gonzalez, Julio (Acta Gymnica, 2023)
Background: In elite soccer, many teams routinely use positional games (PGs) in their practice sessions, striving to simulate competition situations, although some debate exists about the application's usefulness. Objective: The main aim of this descriptive study was to compare the physical demands among three different formats of PGs within the competitive profile. Methods: A descriptive study was conducted with 19 Argentinian professional soccer players (age 23.7 ± 4.7 years, body mass 73.6 ± 7.0 kg, height 177.2 ± 5.6 cm). External load was monitored by GPS (Catapult) during typical practice sessions with PGs designs (7 vs. 7 + 1 Floater [F], 9 vs. 9 + 2F + 2 goalkeepers [GK], 10 vs. 10 + 1F + 2GK) and during 10 official matches. Data on total distance (TD), player-load (PL), HILR (distance covered at speed > 14.9 km/h per minute), HSSL (distance covered at speed > 19.9 km/h per minute), number of runs during HILR and HSSL, very high-intensity accelerations (> 3.5 m/s2; VHIA) and decelerations (< -3.5 m/s2; VHID) and maximal speed (MS) were measured. In addition, rates of perceived exertion (RPE) were also monitored. Results: The mean values of TD and PL were similar to those of match status in every format. With respect to HILR and HSSL, the average values were significantly lower than those obtained in matches for 7 vs. 7 + 1F and 9 vs. 9 + 2F + 2GK formats (p < .001). The MS was the other variable in the study that differed notably from the values obtained during matches in each format (p < .001). The VHIA values were significantly higher than matches in 7 vs. 7 + 1F, while VHID presented statistical differences in both formats, 7 vs. 7 + 1F and 10 vs. 10 + 1F + 2GK. Regarding RPE, 10 vs. 10 + 1F + 2GK was the only format without statistical difference in comparison with matches (p < .001). Conclusions: The findings suggest that smaller-sized PGs could be used to stimulate intensity in terms of acceleration/deceleration demands, whereas larger-sized PGs are the optimum format to reach a similar performance in a competitive situation.
Keywords: sportovci; fotbal; tělesná výkonnost; dospělí; Soccer; Professionalism; týmové sporty; Humans; Athletes; lidé; profesionalita; Sports; Adult; sporty; Team Sports; Physical Fitness